2005
DOI: 10.1017/s0266467405002543
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of secondary forest regrowth after slash-and-burn agriculture in central Amazonia

Abstract: This study describes forest succession following slash-and-burn agriculture in central Amazonia, based on four chronosequences (22 sites) of 2- to 25-y-old secondary regrowth and mature forest. Biomass accumulated in the form of a saturation curve: 25 y of regrowth restored half of the mature-forest biomass, 75% would be restored after an estimated 175 y. Biomass accumulation was accompanied by a rapid decrease in woody plant density and an increase of the positive skew of plant size distribution. Liana biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 56 publications
4
87
1
4
Order By: Relevance
“…Lett.). Compared to recovery following slash-and-burn, the postpasture forests of this study recovered biomass more slowly than Piper-dominated SFs in the humid lowlands of Papua New Guinea (Hartemink 2001), more rapidly than rates reported for Bolivian lowland SFs (Steininger 2000), at similar rates for a review of forest recovery following slash-and-burn in the Tropics (Brown and Lugo 1990), and much lower than after shifting cultivation 50-100 km from our study area (Gehring et al 2005).…”
Section: Forest Structure Developmentsupporting
confidence: 60%
See 2 more Smart Citations
“…Lett.). Compared to recovery following slash-and-burn, the postpasture forests of this study recovered biomass more slowly than Piper-dominated SFs in the humid lowlands of Papua New Guinea (Hartemink 2001), more rapidly than rates reported for Bolivian lowland SFs (Steininger 2000), at similar rates for a review of forest recovery following slash-and-burn in the Tropics (Brown and Lugo 1990), and much lower than after shifting cultivation 50-100 km from our study area (Gehring et al 2005).…”
Section: Forest Structure Developmentsupporting
confidence: 60%
“…Gehring et al (Gehring et al 2005) found that a moderate increase in the intensity of land use had only minor effects on biomass accumulation, but affected forest structure with the biomass being more evenly distributed among size classes. In the upper Rio Negro of the Amazon basin biomass increased linearly through the first 40 yr following clearcutting and abandonment, but did not change for the next 40 yr because of the death of long-lived successional species (Saldarriaga et al.…”
Section: Forest Structure Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased C/N ratio of litterfall with increased degradation is in agreement with observations by Feldpausch et al (2004) along a sequence of secondary forest regeneration in Central Amazonia. During early forest succession the biomass accumulates rapidly and consists mainly of easily decomposable litter and less of wood (Gehring et al 2005;Guariguata and Ostertag 2001). More readily decomposable litter may on the long-term lead to reduced peat accumulation at the degraded sites (Frolking et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance legacy includes frequency of past fires (2) or other disturbances such as slashing (39) or landslides (5). Several studies contain disturbance legacy as a source of variation to understand the role of fires in tropical forests (24,(42)(43)(44)(45) (Table 2).…”
Section: Placing the Soil Burn Severity Index Within The Context Of Tmentioning
confidence: 99%